Therapeutic results and safety of postoperative radiotherapy for keloid after repeated Cesarean section in immediate postpartum period - Kim, Juree; Lee, Sang Hoon (Radiation oncology journal, 2012)
To evaluate the effectiveness and safety of postoperative radiotherapy for the treatment of keloid scars administered immediately after Cesarean section. A total of 26 postpartum patients with confirmed keloids resulting from previous Cesarean sections received either 12 or 15 Gy radiotherapy. The radiotherapy was divided into three 6 MeV electron beam fractions administered during the postpartum period immediately following the final Cesarean section. To evaluate ovarian safety, designated doses of radiation were estimated at the calculated depth of the ovaries using a solid plate phantom and an ionization chamber with the same lead cutout as was used for the treatment of Cesarean section operative scars and a tissue equivalent bolus. In total, the control rate was 77% (20 patients), while six (23%) developed focally elevated keloids (ranging from 0.5 to 2 cm in length) in the middle of the primary abdominal scar. Five patients experienced mild hyperpigmentation. Nonetheless, most patients (96%) were satisfied with the treatment results. The estimated percentage of the applied radiation doses that reached the calculated depth of the ovaries ranged from 0.0033% to 0.0062%. When administered during the immediate postpartum period, postoperative electron beam radiotherapy for repeated Cesarean section scars is generally safe and produces good cosmetic results with minimal toxicity.